2012
DOI: 10.1016/j.ssc.2011.10.023
|View full text |Cite
|
Sign up to set email alerts
|

Impact of substrate on magnetic phase coexistence in bicritical Sm0.53Sr0.47MnO3 thin films

Abstract: Sm 0.53 Sr 0.47 MnO 3 thin films were deposited on single crystal LaAlO 3 (LAO/(001)) and SrTiO 3 (STO/(001)) substrates by DC magnetron sputtering. The -2 and -2 scans show that these films have very good crystallinity and the films on LAO and STO are under compressive and tensile strain, respectively. The films on LAO and STO substrates show ferromagnetic (insulator-metal) transition at T C~1 26 K (at T IM~1 28 K) and 120 K (T IM~1 17K), respectively.The magnetic state at T Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
7
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 17 publications
0
7
0
Order By: Relevance
“…In case of the film on LAO the surface appeared to consist of large and big granules, while in case of the films on LSAT and STO substrates the granule size are more uniform. As compared to single crystalline Sm 0.53 Sr 0.47 MnO 3 thin films prepared by DC magnetron sputtering, 19,22 the surface roughness of these polycrystalline films is relatively higher. The representative surface topographs of films on LAO and STO are presented in Fig.…”
Section: Resultsmentioning
confidence: 95%
See 3 more Smart Citations
“…In case of the film on LAO the surface appeared to consist of large and big granules, while in case of the films on LSAT and STO substrates the granule size are more uniform. As compared to single crystalline Sm 0.53 Sr 0.47 MnO 3 thin films prepared by DC magnetron sputtering, 19,22 the surface roughness of these polycrystalline films is relatively higher. The representative surface topographs of films on LAO and STO are presented in Fig.…”
Section: Resultsmentioning
confidence: 95%
“…Recently, it has been shown that even a very small substrate induced strain could modify the magnetotransport properties in Sm 1-x Sr x MnO 3 (x ∼ 0.5) in the FMM regime (T < T C ). 19,22 In case of textured polycrystalline thin films the nature of the strain state is expected to be drastically different from the single crystalline and epitaxial thin films. In the textured/oriented polycrystalline thin film the local epitaxial regions are interrupted by the presence of GBs and around these regions the strain, irrespective of its nature (whether it is compressive or tensile) is expected to get relaxed.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Shorter annealing time resulted in poor characteristics. Here we would like to mention that annealing at 900 C has been used in case of various manganite thin films [18][19][20][21] and no interdiffusion at the substrate-film interface has been seen either in case of LAO or STO substrates. Annealing temperature higher than 900 C have also been used in several studies.…”
mentioning
confidence: 99%